2021
DOI: 10.1007/s00217-021-03924-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the distillation process on polyphenols content of grape pomace

Abstract: Grape pomace is a winery by-product that is more and more valorized as a source of healthy bioactive molecules such as polyphenols. In addition, it can be used to produce some alcoholic beverages, such as grappa, which is a typical distilled Italian alcoholic product. The spent grape pomace after grappa elaboration is mainly considered a food waste. The aim of this study was to reconsider and valorize red and white pomaces obtained after the production of grappa. The total phenolic content of both samples, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In addition, GP can be used to produce some value-added components such as edible acids (citric, tartaric, and malic acids) and dietary fiber, as well as ethanol (Ilyas et al, 2021 ). Moreover, GP is the starting point for preparing alcoholic spirits like Italian grappa (Cisneros-Yupanqui et al, 2021 ).…”
Section: Grape Pomacementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GP can be used to produce some value-added components such as edible acids (citric, tartaric, and malic acids) and dietary fiber, as well as ethanol (Ilyas et al, 2021 ). Moreover, GP is the starting point for preparing alcoholic spirits like Italian grappa (Cisneros-Yupanqui et al, 2021 ).…”
Section: Grape Pomacementioning
confidence: 99%
“…Moreover, GP is the starting point for preparing alcoholic spirits like Italian grappa (Cisneros-Yupanqui et al, 2021).…”
Section: Grape Pomacementioning
confidence: 99%
“…Distillation also constitutes a common way to economically valorize grape marc for the recovery of ethanol for its further use in the elaboration of alcoholic beverages [21]. In a simplified way, the sugars present in the raw marc are subjected to alcoholic fermentation under anaerobic conditions, followed by the subsequent distillation and the release of vinasses and distilled grape marc as the main waste streams [22].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the pomace employed, red or white, different types of Grappa can be produced (Cisneros‐Yupanqui et al ., 2021). The distillation of grape pomace for grappa production is of great significance in Italy's industrial sector, reaching a production of 74 200 hL of pure alcohol equivalents in 2021 (Associazione Nazionale Industriali Distillatori di Alcoli ed Acquaviti, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to fresh pomace, SGP obtained after the distillation has been little studied so far (Bordiga et al ., 2015). Previous research has shown the potential of SGP as a source of antioxidants since this bioactivity, especially due to the content of phenolic compounds, did not decrease significantly after the distillation of grape pomace (Cisneros‐Yupanqui et al ., 2021), fostering its valorisation.…”
Section: Introductionmentioning
confidence: 99%